(untitled) - Starr, Cecie (Victoria, Australia, 2004)
The 10th edition of this undergraduate text seeks to make students aware of the connection between molecular change, evolution, and students' own lives. To achieve this goal, the text features essays on current controversial issues, links to concepts within and between chapters, two-page concept spreads, and problem solving examples and experiments that encourage students to think critically. Other changes include reorganized and rewritten material on areas such as energy flow and stem cell research. Author information is not given.
Keywords: Biology